Learning During the Covid-19 Pandemic: Correlation Between Income Levels And Parental Roles - Kartika Rinakit Adhe; Rohmatul Maulidiya; Muchamad Arif Al Ardha; Wulan Patria Saroinsong; Sri Widayati (Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 2021)
This study aims to determine the correlation between parental income levels with the role of parents. The sample is 370 parents of affected by Covid-19 pandemic in Indonesia. The method used is a quantitative correlational approach to the type of survey analysis. The results showed the frequency of parents playing with children before and during the pandemic increased from 38.6% to 62.0%. The results of the bivariate correlation analysis are significance values of 9,956 (Sig 0.05) with Pearson correlation coefficient numbers showing a result of -0.003 which means that the correlation only 0.003. The correlation coefficient is negative then correlation is inversely proportional, if the income level is moderate then the role of parents is high and vice versa which means that Ha is rejected and Ho is accepted there is no correlation between the level of parental income with the role of parents in early childhood learning during Covid-19.